KINERJA RANTAI PASOKAN KOPI ARABIKA JAVA PREANGER DI KABUPATEN SUMEDANG JAWA BARAT - Ginanjar, Yayat; Apiatno, Apiatno; Amanda, Helles (E-Jurnal Manajemen; Vol 9 No 11 (2020), 2020)
Sumedang District has featured in many commodities from agricultural sector, but in the agricultural sector there are still many problems, especially coffee. The problem of slow development of the agricultural sector can be seen from the main problems faced by farmers, that in the limitations of managed agricultural land and the status of farmers mostly only farmworkers.Taking into account the problems in the commodity, in improving the competitiveness of a business requires information from the flow of products. Descriptive qualitative methods are selected by researchers, this is to describe the results of research from the supply chain and its value-added analysis. From the results of the research, there are still obstacles faced by business estimators in every supply chain activity, especially in the provision of agro input and cultivation processes that have not supported productivity improvement, limited processing tools, and marketing that has not been integrated between businesses so that its competitiveness is not optimal. Directional and integrative policy is needed from the government to support the coffee business climate in order KAJP East Manglayang can be a featured commodity that can boost people's economic activities, that government policy will determine the productivity of agriculture in the field of coffee. Keywords : cofee, value-added, supply chain